Numerical investigations of flow over a confined circular cylinder - Mathupriya P.; Chan L.; Hasini H.; Ooi A. (Australasian Fluid Mechanics Society, 2023)
Boundary layers; Circular cylinders; Fluid mechanics; Reynolds equation; Reynolds number; Spectrum analysis; Wakes; Confinement effects; Counter rotating; Flow over a cylinder; Lift coefficient; Numerical investigations; Peak frequencies; Shedding frequencies; Three-dimensional flow; Vortex flow